Myth : A Very Short Introduction - Segal, Robert A. (Oxford, New York Oxford University Press, 2015)
This Very Short Introduction explores different approaches to myth from several disciplines, including science, religion, philosophy, literature, and psychology. In this new edition, Robert Segal considers both the future study of myth as well as the impact of areas such as cognitive science and the latest approaches to narrative theory
Include Illustration and Index
Keywords: Myth -- Mythology